2022
DOI: 10.3390/nu14050941
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dietary Patterns and Factors Influencing Food Choice among Ethnic Groups Living in One Locality: A Systematic Review

Abstract: Globally, the number of minority ethnic groups in high-income countries is increasing. However, despite this demographic change, most national food consumption surveys are not representative of ethnically diverse populations. In consequence, many ethnic minorities’ dietary intakes are underreported, meaning that accurate analysis of food intake and nutrient status among these groups is not possible. This systematic review aims to address these gaps and understand differences in dietary intakes and influencers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 85 publications
1
22
0
Order By: Relevance
“…In our study, participants who identified as Hispanics had higher liking ratings for selected fruits, vegetables, and nuts, as well as higher HEI total fruits and sodium scores than those who identified as non-Hispanics. This is supported by a recent systematic review that demonstrates that Hispanics have higher fruit intakes than non-Hispanic Whites (61). Analysis of 24-hour recalls from a cohort of the Hispanic Community Health Study reports that the sodium intake among Hispanics is much higher than recommended intake (62).…”
Section: Discussionmentioning
confidence: 87%
“…In our study, participants who identified as Hispanics had higher liking ratings for selected fruits, vegetables, and nuts, as well as higher HEI total fruits and sodium scores than those who identified as non-Hispanics. This is supported by a recent systematic review that demonstrates that Hispanics have higher fruit intakes than non-Hispanic Whites (61). Analysis of 24-hour recalls from a cohort of the Hispanic Community Health Study reports that the sodium intake among Hispanics is much higher than recommended intake (62).…”
Section: Discussionmentioning
confidence: 87%
“…For example, some epidemiologic studies of IBD have noted that diet has an impact on the incidence of IBD, and specifically diets high in trans-unsaturated fat, red meat and low in fiber may increase the risk of developing IBD 10,11,21 . Data also suggest that dietary consumption patterns differ according to race and ethnicity and may therefore contribute to rise in IBD incidence among US Black individuals 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a lower level of acculturation has been associated with a healthier eating pattern among Latinx immigrants [ 73 ]. Moreover, socio-economic status, education, and income are universal determinants of food choices, including caloric density, across cultural groups in the U.S. and elsewhere [ 74 ]. Food waste has also been documented as being considered “bad” amongst other immigrant groups [ 75 ].…”
Section: Discussionmentioning
confidence: 99%